Status of work accidents in food industry - Evtushenko, Olga; Klepikov, Igor; Litvinenko, Anatoly (My University, 2013)
We show the results of occupational injury dynamic research in Food Industry of Ukraine from 2003 to 2011. Distribution for male and female injured employees on enterprises of Food Industry was performed. Indexes of injury rate and heaviness were calculated. And finally, distribution of accidents for main reasons, sorts of events, profession group, age, work experience was performed.
Keywords: виробничий травматизм; нещасний випадок; травматизм; кафедра екології та екоменеджменту